Evaluation of a Group-Specific 16S Ribosomal DNA-Based PCR for Detection of Helicobacter bizzozeronii, Helicobacter felis, and Helicobacter salomonis in Fresh and Paraffin-Embedded Gastric Biopsy Specimens - De Groote, Dominic (American Society for Microbiology, 2001)
A new specific and sensitive 16S ribosomal DNA-based PCR assay was developed. The assay targets a 78-bp DNA fragment unique to Helicobacter bizzozeronii, Helicobacter felis, and Helicobacter salomonis and can be used with freshly frozen and formalin-fixed paraffin-embedded gastric biopsy specimens.